Kritik atas Kritik Kamaruddin Amin terhadap Riwayat MudallisÄ«n dalam á¹¢aá¸¥Ä«á¸¥ al-BukhÄrÄ« dan á¹¢aá¸¥Ä«á¸¥ Muslim - Syukrillah, M. (Fakultas Ushuluddin, Adab dan Humaniora Institut Agama Islam Negeri (IAIN) Jember, 2017)
This research is prompted by the thought of Kamaruddin Amin who challenges the concept of â€˜UlÅ«m al-á¸¤adÄ«th about the transmission of mudallisÄ«n in the á¹¢ahÄ«á¸¥ al-BukhÄrÄ« and á¹¢ahÄ«á¸¥ MuslÄ«m. The article finds that: first, there have been inconsistencies and gaps between the theory and practice in the concept of tadlÄ«s; second, there are negative implications of application of tadlÄ«s according to â€˜UlÅ«m al-á¸¤adÄ«th against the transmission of mudallisÄ«n; third, á¹¢Ä«ghat al-Taá¸¥ammul wa al-AdÄâ€™ has no significance either in the study of á¸¥adÄ«th authentication in general or in the context of tadlÄ«s in particular; fourth, NÄsir al-DÄ«n al-AlbÄnÄ«â€™s method of determining the authenticity of mudallas á¸¥adÄ«th has a weakness and negative implications upon mudallas á¸¥adÄ«ths in general; fifth, the application of mudallas á¸¥adÄ«th criticism according to the traditional method using al-jará¸¥ muqaddam â€˜alÄ al-taâ€˜dÄ«l idhÄ kÄnÄ mufassaran when the controversy occurs in the assessment of the predicate of a á¸¥adÄ«th; and sixth, orientalistâ€™s method of giving the calendar to the á¸¥adÄ«th can be used as an alternative way to overcome the weaknesses of the method of classical á¸¥adÄ«th science.